O valor da cultura: avaliação de projetos artístico-culturais no âmbito individual e coletivo - PEREIRA, Milena Alves Mourão (2019)
The present study arises from the following question: what is the value of investing in art and culture in these times? In this spectrum, in which society gradually recognizes culture as a resource for development, there is another fundamental problem to be explored, and it concerns the field of culture evaluation. Measuring the resonance of cultural initiatives and at what level it impacts individuals and society is a fundamental process in the recognition of its value, not only to state its significance in the scope of social and economic promotion, but also to show how it is a mechanism that enriches and affects humans subjectively. Therefore, experts in the field warn that valuing culture cannot be done under the same dynamic of other sectors and bring relevant criticism to the methods that institutions are evaluating their investments in the sector. Therefore, for an accurate view of the phenomenon, the qualitative research is the most adequate due to the intangible specificity. In this sense, the objective of the research is to identify how an artistic-cultural project impacts on the individual and collective scope, taking as a case the Coral of the Federal University of Maranhão In this scenario, as an additional objective, the aim is to situate the university's role in the cultural and political system, since extension is one of the channels of access and cultural enjoyment in society. An anchored theoretically in several approaches of the significance of the culture, the Guetzkow (2002) impact model of the arts for the construction of the categories was chosen, as well as the contribution of the studies of Holden (2004, 2006) when proposing new looks to the subject of the value of culture. The methodological course of the study has an exploratory and descriptive characteristic. In addition to the bibliographic review, there was the adoption of field research, using the semi-structured interview. The results reveal meanings that reflect on individual and collective impacts, corroborating how art and culture contribute to artistic development and personal well-being, and to the same extent, provide opportunities for inclusion, manifestations of citizenship and expansion vision of the project participants. As a contribution, it is intended that this method of work can be used in other cultural projects, disseminating the discussion about the value of culture.